Growth performance, body conformation, carcass characteristics and palatability of Kedah-Kelantan cattle and its crosses - Ismail, Dahlan (1985)
The growth performance, of 423 heads of male and .female Kedah-Kelantan (KK)cattle and its F1 crosses were recorded from the same grazing management. Comparisons were: made between progenies of KK cows sired by straight bred KK, American Brahman (Br), Polled Hereford (Hr), Friesian (Fr) and Jersey (Jy). The main objectives of this experiment was to evaluate the simplest crossbreeding system of KK cattle by straight cross between KK female and exotic male for the advantage of heterosis in the growth performance, conformation, carcass characteristics and meat palatability in the F1 generation. The present result showed that all the F1 crossbreds heifers and bulls were superior in the growth performance than the straight bred KK at all' ages. All crossbred calves had significantly higher (P < 0.01) birth weight than KK. Brahman x KK(BK)calves were the heaviest at birth, followed by Friesian x KK(FK), Hereford x KK(HK)and Jersey x KK(JK), respectively. The overall percent advantage of crossbreds at birth ~t over KK was 27.13%. FK was the heaviest at the adjusted 200-day weight, followed by HK, BK, JK and KK respectily. All crossbreds calves were showing better pre-weaning grow~ ability than the KK. HK showed superiority in post weaning growth performance than the other crossbreds. Ranking of sire breeds by using the slope of regression equation of growth-age lines as the estimate of growth rate, breed type among years. generally showed consistency for the Under similar management unit and one type of maternal environment, the result showed that treed sire, especially temperate sires" had contributed the main effect on all the growth traits of these calves. HK showed higher conformation score due to the tendency of the beef breed crosses to fatten at lighter weight than the dairy breed crosses. HK and FK had the longest body, FK was the tallest at wither, BK was the tallest at the hip, KK was the shortest cattle. HK was the shortest among the crossbreds at the hip. There is evidence for breed difference in the ~ament. This study concluded that Bos indicus cattle and crosses (Brahman x KK)were having poor temperament than half-bred cattle (FK, HK and JK). The result of carcass evaluation concluded that breed of sire had no significant effect on factor associated with dressing percentage but had significant effect (P < 0.05) on the carcass weight per day of age (CWDA). All the crossbreds showed higher CWDA than KK in all slaughter weight group. HI< showed the highest CWDA and 21 to 44%superior than KK as the animal increases in slaughter weight. Animals sired by beef type (Hr and Br) produced higher percentage of hindquarter than the crosses from dairy type (Fr and Jy). HI< showed the biggest (p < 0.05) loin eye area in all slaughter weight group. KK bulls showed lower bone can position and higher lean composition than other breed type under similar weight group. Fat composition in the carcass of Zebu cattle (KK and BK) was higher than Zebux temperate cattle. Comparison of palatability scores between breed type revealed no significant difference but the scores significantly decreased (P < 0.05) as the cattle increased in age from 28- month to 40-month. Among breed types, FK and BK showed higher shear force values than JK, HI< and KK. The present result concluded that .ultimate muscle pH of all breed types have sane effect on the flavour, overall palatability, tenderness and cooking loss. The best single body measurement for prediction of total lean meat of half carcass was the measurement of heart girth and the best 4 combination of body measurements found were heart girth, width of loin, flank girth and width of head. Carcass measurements were also used for predictions of total lean meat. The result showed that forequarter weight, loin eye area, meat to bone ratio, carcass length and dressing percentage are the best 5 variables that should be used in the combination.